Diagnostic work-up in peripheral neuropathy: an analysis of 171 cases. Issue 890 (1st December 1999) - Lubec, Doris; Müllbacher, Wolf; Finsterer, Josef; Mamoli, Bruno
Abstract : This study was set up to evaluate retrospectively the efficacy of a standard diagnostic procedure, including non-invasive and invasive (spinal tap, nerve/muscle biopsy) investigations, in the diagnosis of peripheral neuropathy. The medical records of 171 in-patients with the final diagnosis of peripheral neuropathy of determined or undetermined cause were reviewed and each individual diagnostic work-up was analysed. Basic investigations included the patient's history, a clinical examination and basic laboratory tests. Depending on the individual presentation, course, and severity, further non-invasive and invasive examinations were added according to the department's standard diagnostic procedure. The aetiology could be clarified in 124 patients (73%) and remained unclear in 47 cases. Excluding cases with acute and chronic inflammatory polyneuropathy ( n =14), the number of idiopathic peripheral neuropathies dropped to 33. Non-invasive investigations were sufficient to reveal the underlying aetiology in 114 cases (83 %). It is concluded that, with the application of a standard procedure for the diagnosis of peripheral neuropathy, the aetiology can be clarified in 81% of patients. In the other 19% of patients the aetiology remains idiopathic. In the majority of cases, non-invasive investigations were sufficient for diagnosis.